KAJIAN WACANA DAMPAK PENGGUNAAN GADGET (GAWAI) TERHADAP KEMAMPUAN SOSIAL EMOSIONAL PADA ANAK USIA DINI - Intan Nur Laily; Ratnasari Dwi Ade Chandra (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2021)
This research is motivated by the use of gadgets in early childhood which has positive and negative impacts, one of which is in children's social emotional abilities. Most parents do not understand the impact of using gadgets on children, providing gadgets to children so as not to interfere with parents' activities, introducing technology from an early age and making friends in cyberspace which will affect the child's social emotional ability in fact, social emotional abilities in children really need to be developed from an early age so that children grow and develop as expected. Therefore, research is needed on the impact of gadget use on socio-emotional abilities in early childhood. This research includes literature research with a qualitative research approach. Sources of data taken are from library data in the form of books and research journals in accordance with the study to be studied. The results of the study explain that the use of gadgets in early childhood has an impact on children's social emotional abilities.